Stratified citizenship, stratified health: Examining latinx legal status in the U.S. healthcare safety net - Van Natta, Meredith (Soc Sci Med, 2018)
Our paper explores how legal status stratification shapes the health and health care of low-income patients with chronic illnesses in the U.S. healthcare safety net. Drawing on data from over two years of ethnographic fieldwork at urban safety-net clinics, we examine e fforts by Complex Care Management (CCM) teams to stabilize patients with uncontrolled chronic illnesses through primary care-integrated support. We show that stratified citizenship and geographic variability correspond to different possibilities for health care. We suggest an approach to immigration as a structural determinant of health that accounts for the complex, stratified, and changing nature of citizenship status. We also highlight how geographical differences and interactions among local, state, and federal policies support the notion that citizenship is stratified across multiple tiers with distinctive possibilities and constraints for health. While county-based health plans at each of the study sites include residents with varying legal status, lack of formal legal status remains a substantial obstacle to care. Many immigrants are unable to take full advantage of primary and specialty care, resulting in unnecessary morbidity and mortality. In some cases, patients have returned to their country of origin to die. While CCM teams provide an impressive level of support to assist immigrant patients in navigating healthcare and immigration bureaucracies, legal and geographic stratification limit their ability to address broader aspects of these patients’ social context.